Diminishing benefits of thermal mass in Iranian climate: Present and future scenarios - Rodrigues, Eugénio (2024)
Thermal mass, a pivotal element in a building’s performance, functions as an indoor thermal buffer. While literature underscores its advantages, the enduring impact of thermal mass amid climate change remains uncertain. This study methodically assesses thermal mass effects in 21 Iranian cities across contemporary and future climates, juxtaposing heavyweight and lightweight constructions. The EPSAP algorithm, a generative building design method, created a dataset of two-story single-family houses. Cooling and heating demands were evaluated in EnergyPlus, accounting for current and future system design efficiencies. Future climates were simulated using EC-Earth3 model estimations for the SSP5-8.5 scenario in 2050 and 2080 timeframes. The findings reveal that the energy efficiency advantage of heavyweight over lightweight buildings will diminish by up to 0.60 kW⋅h⋅m− 2 in 2050 (40 % less than the present-day climate difference between constructions) and 0.93 kW⋅h⋅m− 2 in 2080 (63 %) for cities in central and southern regions. The performance differences between constructions will sometimes be null, making thermal mass negligible. Conversely, only three cities in Northern Iran exhibit an opposing trend for mid to very-high thermal transmittances. Regarding building geometry, heavyweight construction correlates strongly with indexes related to building compactness, while lightweight construction aligns more with glazing-related indexes. However, as climates warm or we move towards warmer regions, discernible differences between lightweight and heavyweight constructions vanish for both shape- and glazing-related indexes. In conclusion, although the use of thermal mass will be less effective, building design professionals will have greater latitude for innovative construction and design solutions.